PENINGKATAN KEMAMPUAN MEMBACA PERMULAAN PESERTA DIDIK MELALUI MEDIA KARTU HURUF PADA MATA PELAJARAN BAHASA INDONESIA DI KELAS II SD INPRES LILI KABUPATEN KUPANG: Penelitian Tindakan Kelas - Lodo Nawa, Hesty Octaviani; Markus Sampe; Kurniayu T. R. A. Ratu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Research results by Hesty Octaviani Lodo Nawa Nim 2101140069 with the title Improving Students' Beginning Reading Skills Through Letter Card Media in Indonesian Language Subjects in Grade 2 of UPTD SD Inpres Lili, Kupang Regency. With the formulation of the problem: "Can the Use of Letter Card Media in Indonesian Language Learning Improve the Early Reading Skills of Grade II Students at UPTD SD Inpres Lili, Kupang Regency?" Objective: "To find out the Improvement in Early Reading Results in Indonesian Language Learning with the Use of Letter Card Media in Grade II UPTD SD Inpres Lili, Kupang Regency." Data collection was conducted using observation and testing techniques. Data analysis techniques used descriptive quantitative and qualitative methods. The study involved 21 subjects, 14 males and 7 females. This research was conducted at the Lili Inpres Elementary School (UPTD SD Inpres Lili). The results showed that in Cycle I, 11 of the 21 students (52.38%) completed the coursework. This was due to their active involvement in the learning process, understanding the material presented by the teacher, and working collaboratively in groups to complete the worksheets assigned by the teacher. Meanwhile, 10 students (47.61%) did not complete the coursework due to a lack of concentration during learning activities, a lack of collaboration with their group mates, and a tendency to tell stories and play during the lesson. Furthermore, in Cycle II, student learning outcomes improved, with 19 of the 21 students (90.47%) completing the coursework. This was due to more active, concentrated, and directly involved learning activities, as well as working collaboratively in groups to complete the worksheets assigned by the teacher. Based on the research results and discussion above, it can be concluded that the use of the problem-based learning model can improve students' learning outcomes in the material on reading words that are often encountered every day at the UPTD SD Inpres Lili.